Non-Shortest Paths Route Choice Model Based on Fuzzy Preference Relations - Ridwan, M. (Center for Research and Community Services ITB, 2003)
This paper presents a new methodology for route based on fuzzy preference relations. The core of the model is FiPV (fuzzy-individualle Praeferenzen von Verkehrstilnehmern or fuzzy traveler preferences) , that is an adjustment of Orlovsky‘s fuzzy choice function for travel decisions. The proposed model is the first application of fuzzy individual (preference-based) choice in travel demand modeling and also the first in this class to consider spatial knowledge of individual travelers in route choice. It is argued that travelers do not or cannot always follow perfect maximization principle. We formulate therefore a model that also takes into account the travelers with non-perfect maximizing behavior. Although the model is not yet supported by empirical evidence, it shows a more transparent structure than those of/he Conventional dynamic route Choice models.